Tracking Master of Public Health graduates: Linking higher education and the labour market - T Dlungwane; S Knight (South African Medical Association, 2016)
Background. Master of Public Health (MPH) students come from a wide range of health professional backgrounds. Graduate programmes in public health should equip alumni with knowledge and skills to analyse and integrate health research findings, and have a practical approach to current public health issues. In South Africa (SA), there is a need for health professionals with an adaptable public health approach who can contribute meaningfully to addressing public health problems and transforming the health sector. The role and relevance of graduate public health training in the SA healthcare system have not yet been reported. Tracking of graduates is important to assess the effectiveness of study programmes, graduates’ worth for the healthcare labour market, and their contribution towards improving the healthcare system.Objective. To describe the professional backgrounds of MPH graduates from the University of KwaZulu-Natal, Durban, SA and the role of their learning in their current public health practice.Methods. An emailed, self-administered questionnaire survey of graduates (N=61) was conducted in 2013.Results. Forty-five (73%) of the 61 contactable public health graduates from the past 10 years returned the completed questionnaire; 28 (63%) areworking in the public sector and 9 (22%) at academic institutions. Graduates reported that research skills, critical analysis, report writing, and leadershipand management were acquired in the MPH programme. Most reported that they were able to integrate the knowledge and skills acquired from the MPH degree in their current workplace.Conclusion. The MPH degree equips graduates with skills that contribute to addressing some of the public health problems in SA.